Thrixspermum merguense (Hook.f.) Kze. (Orchidaceae) a new record for the Andaman Islands and Indian flora - Mathew, S.P. (2014)
Thrixspermum merguense (Hook.f.) Kze. belonging to the family Orchidaceae has been described and illustrated as a new record for Indian flora.